Privatization in Economic Theory - Drakić, Maja (Panoeconomicus, 2007)
In reality privatization has never occurred according to the handbook rules of ordinary market transactions. Not even in advanced market economies can privatization transactions be described by the Walrasian or Arrowian, or Leontiefian equilibrium models, or by the equilibrium models of the game theory. In these economies transactions of privatization take place in a fairly organic way – which means that those are driven by the dominance of private property rights and in a market economy. But despite this fact Western privatization also some peculiar features as compared to ordinary company takeovers, since the state as the seller may pursue non – economic goals. Changes in the dominant form of property change positions and status of many individuals and groups in the society. That’s why privatization can even less be explained by ordinary market mechanisms in transition countries where privatizing state-owned property have happened in a mass scale and where markets and private property rights weren't established at the time process of privatization began. In this paper I’ll discuss and analyze the phenomenon of privatization in context of different economic theories arguing that empirical results go in favor of the public choice theory (Buchanan, 1978), theory of "economic constitution" (Brennan and Buchanan 1985), (Buchanan and Tullock, 1989), and theory of "collective action" (Olson, 1982). These theories argues that transition from one economic system into another, for example transition from collectivistic, socialistic system into capitalism and free market economy with dominant private property, will not happen through isolated changes of only few economic institutions, no matter how deep that changes would be. In other words privatization can not give results if it's not followed by comprehensive change of economic system because privatized companied wouldn't be able to operate in old environment.Key words: Private property rights, Privatization, Transaction, Institutions, Transition.JEL: L33, P48.